Effects of performing endurance and strength or plyometric training concurrently on running economy and performance - Lum, D. (Strength and Conditioning Journal, 2016)
Both strength and plyometric training have been shown to benefit endurance running performance. One of the benefits is that such training methods help to improve running economy through improved neuromuscular adaptations. However, there are some studies that show an interference effect with concurrent strength and endurance training. The purpose of this article is to elucidate the benefits of strength and plyometric training for endurance runners and provide coaches and runners with information for concurrent endurance and strength or plyometric training.